Changes in circulating inflammatory markers following febrile non‐haemolytic transfusion reactions to leucoreduced red cells. Issue 1 (11th October 2017) - Larsen, R.; Sandhu, N.; Heegaard, N. H. H.; Ullum, H.; von Stemann, J. H.; Sørensen, E.; Nellemann, D. S.; Hansen, M. B.
Abstract : It would be desirable to be able to distinguish fever as a result of febrile non‐haemolytic transfusion reactions (FNHTR) from other febrile conditions. To further characterize the inflammatory feature of FNHTR, we measured a large panel of inflammatory markers in pre‐ and posttransfusion plasma samples from patients with and without FNHTR following the transfusion of leucoreduced red blood cells. As FNHTR patients only displayed a significant increase in IL‐6, we conclude that changes in plasma cytokine levels during FNHTR are unlikely to be used diagnostically. An incidental finding of a distinct cytokine pattern in pretransfusion samples from FNHTR patients warrants further investigations, as it might be used to characterize the nature of FNHTR and to predict the risk of these adverse events.